MUSICAL COMPOSITIONS AND FRACTURES: LEAVING TRACES IN MATERIAL, TECHNIQUE, AND THOUGHT - Ahvenniemi, Rebecka Sofia (The Nordic Journal of Aesthetics, 2022)
“Each and every important work of art leaves traces behind in its material and technique,” Theodor W. Adorno postulates in Aesthetic Theory, as he describes the way a composition is both a result of its own time and reacts critically to the time it belongs to. This quote demonstrates a reversal: rather than merely an expression or an outcome of an artist’s idea, art itself is regarded as a source for change. The work may come to affect its own tools and materials and the social space around it. The primary question of this article is: what is it in musical composition that leaves the traces? This article attempts to move the focus away from discussion of finished works, and instead, depict how composition as a discipline engages in dialogue with its handcraft, historicity, and surrounding social world. I call this aspect of composition that possesses critical potential a lingering reflection. Slow and heteronomous in its nature, it presents a counterpoint to ideas that seem solid, are easily accessible and unquestioned.